STRATEGI KOMUNIKASI PEMASARAN HOTEL KARTIKA GRAHA MALANG DALAM MENINGKATKAN JUMLAH PENGUNJUNG - Ekalista, Peligia; Tri Hardianto, Willy (Jurnal Komunikasi Nusantara, 2019)
Marketing Communication Strategy is a planning to consume products to targeted markets to achieve the company goals. Through marketing communication strategies, companies try to disseminate information, influence, persuade or remind the target market about a message of the company and its products to be accepted, buy the products offered by the company. This research used descriptive qualitative research. This research was conducted at Hotel Kartika Graha Malang, with a purposive sampling technique with data collection techniques. While the technique of data collection was done by observation, in-depth interviews, and documentation. The data analysis technique used data reduction, data presentation and conclusion withdrawing. The results of this study showed that Kartika Graha Hotel Malang used the IMC theory which implemented Marketing Commucation, Sales Promotion, and Marketing Event and also used the Kotler theory included the marketing mix with four P (4P) namely Product, Price, Place, and Promotion. While the supporting factors in marketing communication strategies were the solid and also the application of elements of marketing communication  maximally  and adequate products and facilities. The inhibiting factors in implementing the marketing communication strategy were the lack of human resources such as driver and technicians that caused clashes with other departments and also budget problems such as the late disbursement from the specified date.